OPTIMALIZATION OF INTERPERSONAL INTELLIGENCE OF EARLY CHILDHOOD IN INTEGRATED STATE PAUD (EARLY CHILDHOOD EDUCATION) IN KUTAI TIMUR REGENCY - RAHARDJO, BUDI; MARHAEDAH, MARHAEDAH (Sriwijaya University Learning and Education International Conference, 2016)
These study aimed: (1) To obtain in-depth information of the teachersâ approach inoptimalization interpersonal intelligence in early childhood in State PAUD (EarlyChildhood Education) in Kutai Timur Regency, (2) To obtain in-depth informationof the methods and strategies used by the teachers in the process of optimalization ofinterpersonal intelligence in early childhood in State PAUD (Early ChildhoodEducation) in Kutai Timur Regency, and (3) To obtain a deep information on thedevelopment of interpersonal intelligence of early childhood in State PAUD (EarlyChildhood Education) in Kutai Timur Regency. The method performed in thecollecting and recording of data include: (1) method of participant observation(participant observation), used as the primary method for collecting data of earlychildhood interpersonal intelligence in Integrated State PAUD (Early ChildhoodEducation) in East Kutai Timur Regency, (2) the method of significant interviewcommitted to the Principle, teachers, and students of the Early Childhood Education(PAUD) , and (3) documentation method, as a supporting method to obtaindata/facts. Data analysis technique used were undergone several stages. First, thedata which were obtained from various dah athe characteristics of each. Dataobtained from the recording were transcribed and categorized. Secondly, the datawhich had been transcribed and categorized then were analyzed by using a groupedstage flow model analysis, which begins with (a) data reduction, (b) datapresentation, and (c) drawing conclusions and verification. The results showed are asfollows: (1) Teachersâ approach in the optimalization of early childhoodinterpersonal intelligence are generally divided into two types, namely classical andindividual., (2) Methods and strategies used in the process of optimalizationinterpersonal intelligence of early childhood in Integrated State Early ChildhoodEducation (PAUD) in Kutai Timur Regency is storytelling and playing. and (3)Development of interpersonal intelligence of early childhood in Integrated StateEarly Childhood Education (PAUD) of Kutai Timur Regency, found a significantchange which could be seen from those who were timid, shy, could not cooperate,and neglectful to others, become a brave, always cooperate and empathy.